Methicillin-resistant Staphylococcus aureus along the beef production line: Phenotypic resistance and mecA phylogeny in two ethiopian municipal abattoirs - Samuel Abie; Solomon Lulie Abey; Gashaw Getaneh Dagnaw; Wassie Molla; Mebrie Zemene Kinde; Seleshe Nigatu; Mebrat Ejo; Habtamu Tassew; Anmaw Shite Abat; Eyerusalem Belay; Shimelis Dagnachew; Abebe Tesfaye Gessese; et al. (PLoS ONE, 2026)
Staphylococcus aureus (S. aureus) is a common zoonotic bacteria, responsible for a wide range of infections and is well known for developing resistance to multiple antibiotics. In Ethiopia, information on methicillin-resistant S. aureus (MRSA), particularly from a One-Health perspective, is limited. This study aimed to detect S. aureus , identify MRSA strains, and assess their antibiogram patterns in swab samples collected from two municipal abattoirs in Northwest Ethiopia. A cross-sectional study was conducted between January 2021 and April 2022. A total of 150 swab samples were collected from beef carcasses, abattoir equipment, surfaces, workers’ hands and clothes. Isolation and identification of S. aureus followed ISO 6888−2 standards. Antimicrobial susceptibility was tested against ten commonly used antibiotics using the disk diffusion method. Conventional PCR was used for detection of the mecA gene and Sanger method was used for sequencing. Overall, S. aureus was isolated from 25.3% (38/150) of the samples. The prevalence of S. aureus was 27.1% in beef carcasses, 26.9% in abattoir workers, and 23.1% in the abattoir environment. The prevalence was 22.7% in Bahir Dar and 28.0% in Debre Markos abattoirs. The highest detection rate (35.7%) was from workers’ hands and hooks, while the lowest (11.1%) was from splitting axes. All isolates were susceptible to gentamicin but resistant to penicillin and methicillin. Multidrug resistance was observed in 60.5% of the isolates. Sequencing and phylogenetic analysis of the mecA gene showed that the current isolates were highly similar and clustered closely with mecA from Staphylococcus capitis and Staphylococcus fleurettii , but were distinct from other S. aureus strains. The detection of S. aureus and MRSA in beef carcasses, abattoir environments, and workers highlights potential risks to workers, consumers, and surrounding environments exposed to abattoir waste. Strengthening hygiene and sanitary practices in abattoirs is essential within a One Health framework.